2023
DOI: 10.3390/en16196932
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis and Combustion Behavior of Flax Straw as Biomass: Evaluation of Kinetic, Thermodynamic Parameters, and Qualitative Analysis of Degradation Products

Bahareh Vafakish,
Amin Babaei-Ghazvini,
Mahmood Ebadian
et al.

Abstract: This study describes an investigation of the pyrolysis and combustion of flax straw as biofuel, focusing on the physicochemical properties and kinetic and thermodynamic parameters, and evaluates the type of degradation products using the thermogravimetry analysis–Fourier transform infrared spectroscopy (TGA-FTIR) technique. Pyrolysis and combustion processes were studied via thermogravimetric analysis at different heating rates of 5-10-15 and 20 °C min, one using three isoconversional methods and one using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Pyrolysis is one such process which is used in numerous variations that results in the production of biochar, bio‐oil and syn gas as by‐products that finds wide variety of applications. The combustion and pyrolysis behaviour of flax straw have been studied by researchers and reported that the products obtained during pyrolysis of flax straw could be used as in the field of bioenergy [7] . Wen et al demonstrated the usage of digestate derived from agricultural residues by subjecting it to pyrolytic degradation along with hydrothermal carbonization and observed a enhanced yield of syn gas with higher percentage of H 2 gas [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis is one such process which is used in numerous variations that results in the production of biochar, bio‐oil and syn gas as by‐products that finds wide variety of applications. The combustion and pyrolysis behaviour of flax straw have been studied by researchers and reported that the products obtained during pyrolysis of flax straw could be used as in the field of bioenergy [7] . Wen et al demonstrated the usage of digestate derived from agricultural residues by subjecting it to pyrolytic degradation along with hydrothermal carbonization and observed a enhanced yield of syn gas with higher percentage of H 2 gas [8] .…”
Section: Introductionmentioning
confidence: 99%